Acute haemodynamic effects of metoprolol in hypertensive patients. - Sannerstedt, R (1977)
1. The acute haemodynamic effects of metoprolol (0.15 mg/kg body weight) intravenously were studied at rest and during exercise, in a recumbent position in five patients with arterial hypertension of WHO Stage 1 or 2. 2. Significant decreases in heart rate, cardiac output and arterial blood pressures, both at rest and during exercise, were seen. There were no changes in the calculated stroke volume or systemic vascular resistance. 3. The apparent absence of any relative preponderance of the alpha-adrenoreceptors after acute beta-adrenoreceptor blockade with metoprolol warrants further studies on metoprolol in arterial hypertension.